2008
DOI: 10.1002/tox.20386
|View full text |Cite
|
Sign up to set email alerts
|

Synergist efficacy of piperonyl butoxide with deltamethrin as pyrethroid insecticide on Culex tritaeniorhynchus (Diptera: Culicidae) and other mosquitoe species

Abstract: Continuous and indiscriminate use of pesticides, especially in tropical countries for public health or agriculture purpose, has led many vector populations to become resistant to organochlorides, organophosphates, and even to carbamates and pyrethroids. Development of resistance by a vector population has been one of the reasons for the failure of the control measures in many countries. This investigation demonstrates the efficacy of piperonyl-butoxide (PBO) with deltamethrin, as pyrethroid insecticide, agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Sabadilla is a powder made by seeds of Schoenocaulon officinale , and its activity has been attributed to the alkaloids sabadine, cevadine, and veratridine []. Finally, piperonyl‐butoxide is commonly used as synergist compound when it is mixed with some biopesticides (e.g., pyrethrins) to increase toxicity and produce longer residual action [], although in general it is not certified to be used on organic crops.…”
Section: Introductionmentioning
confidence: 99%
“…Sabadilla is a powder made by seeds of Schoenocaulon officinale , and its activity has been attributed to the alkaloids sabadine, cevadine, and veratridine []. Finally, piperonyl‐butoxide is commonly used as synergist compound when it is mixed with some biopesticides (e.g., pyrethrins) to increase toxicity and produce longer residual action [], although in general it is not certified to be used on organic crops.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively documented that PBO can enhance the effects of insecticidal action, both in the laboratory and in the field 23–31. This report demonstrates that such enhancement can be found in the field against pollen beetle on rape, using tau‐fluvalinate.…”
Section: Resultsmentioning
confidence: 56%
“…Accordingly, a diagnostic dose has been identified that can be recommended for each of the insecticides for the mosquito control programme in the BBMP region (Table ). However, deltamethrin and lambda‐cyhalothrin, recommended by WHO as adulticides, are known to have a very high larvicidal activity against various species of mosquito as well, and hence have been used for the given study.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of mosquito larvae to deltamethrin and lambda‐cyhalothrin is inevitable, as they are being used continuously against agricultural pests. Although these two insecticides are recommended by WHO as adulticides for use in vector control programmes, they do posses a very high larvicidal activity against various species of mosquito as well . Against this background, effective discriminating doses are also presented for deltamethrin and lambda‐cyhalothrin for mosquito larval control within BBMP.…”
Section: Discussionmentioning
confidence: 99%